Effect of Gibberellin, Foliartal Foliar Fertilizer and Growing Medium in Leaves Content of Active substance of Oleander Plant (Nerium oleander L.) - A. A., Yaseen; D. A. K., Jamil (Al-Qadisiyah Journal of Pure Science, 2018)
A pot experiment was conducted in a plantation affiliated to the Al-Diwaniya city during the winter season of (2012 – 2013) to find out effect of gibberellin, foliartal foliar fertilizer and growing medium in leaves content of active substance of oleander plant (Nerium oleander L.). The design of the experiment was randomized complete blocks (RCBD) in a factorial arrangement with three replicates in organizing the workers for the three factors, first factor included four concentrations of gibberellin (0, 250, 500 and 750) mg. L-1, the second factor included four concentrations of Foliartal foliar fertilizer (0, 250, 500 and 750) ml. L-1, the third factor included three growing medium (1 patmos: 2 sand, 1 patmos: 2 clay and 1 patmos: 2 silt). Means were compared by using averages of revised least significant difference (RLSD) at 0.05 probability level when the treatments referred to significant effect. Results showed: 1-The concentrations of active substances (neriin, oleandrin, digitoxingenin and α-tocopherol) recording by effect of GA3 (750 mg. L-1). 2-The foliar fertilizer by the concentration of 750 ml. L-1 increased concentration of active substance (neriine and oleandrin) while 500 mg. L-1 of foliar fertilizer increased concentration of active substances (digitoxigenin and α-tocopherol) in the leaves. 3-Growing medium (1 patmos: 2 silt) increased of active substance concentration (neriine and oleandrin) in the leaves, while growing medium (1 patmos: 2 sand), significantly increased concentration of digitoxigenin and α-tocopherol in the leaves. 4-The interaction between GA3 and foliar fertilizer by combinations of (250 mg.L-1 GA3 and 750 ml. L-1 foliar fertilizer or 500 mg.L-1 GA3 and 500 ml. L-1 foliar fertilizer) increased in most studied characters of oleander plant. 5-GA3 by 250 mg. L-1 and growing medium of 1 patmos: 2 silt superior in concentration of active substance (neriine and oleandrin) in the leaves while combinations of 750 mg. L-1 GA3 with growing medium (1 patmos: 2 sand) that superior with concentration of the active substance digitoxigenin and α-tocopherol in the leaves. 6-Foliar fertilizer by 750 ml. L-1 and growing medium of 1 patmos: 2 silt superior in concentration of active substance (neriine and oleandrin) in the leaves. Combinations of 750 ml. L-1 fertilizer with soil type (1 patmos:2 sand) that superior with concentration of the active substance α-tocopherol. Combination of 500 ml. L-1 with 1 patmos:2 sand increased the concentration of the active substance Digitoxigenin in the leaves. 7-Triple interaction between the factors revealed a significant improvement of the oleander plant in leaves content of active substances, especially with the combinations constituent of GA3 and foliar fertilizer concentrations with growing medium of 1 patmos: 2 silt and 1 patmos:2 sand.